Educational measurement - Lindeman, Richard H.; Merenda, Peter F. (Glenview, Illinois : Scott, Foresman, 1979)
In this second edition of Educational Measurement, we have incorporated recent developments in measurement that we consider important to prospective teachers. New topics include criterion-referenced tests, the role of special projects such as reports and notebooks in classroom measurement, legal considerations in using measurement devices and reporting results, and the use of measurement in teacher-managed, student self-evaluation. The treatment of several topics has been expanded, including the use of tests in the evaluation of instruction, the validity and reliability of measurement devices, the writing of test items, and the use of test results in evaluation of student progress.
Chapter 1. The Nature and scope of measurement in education -- Chapter 2. basic statistics -- Chapter 3. Judging the quality of a measurement instrument -- Chapter 4. Construction and analysis of classroom achievement tests -- Chapter 5. Other measures of pupil progress -- Chapter 6. Pupil Evaluation: marking and reporting.
Includes bibliographical references and index.
Keywords: EDUCATIONAL MEASUREMENT